CUSTOMER SATISFACTION EVALUATION FOR ONLINE FOOD SERVICE DELIVERY SYSTEM IN MALAYSIA - Norshita Mat Nayan; Mohd Khairul Azmi Hassan (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2020)
The food delivery service industry is growing up and has a good potential rate in Malaysia and globally now. With social distancing the new norm, consumers are demanding to have takeout food delivered in parallel with government standard procedure in the Covid-19 pandemic. This research was conducted to examine the satisfaction of customers by using online food delivery services in Malaysia using a quantitative method. It will deal with consumer behaviour, needs, and user requirement elements in analysing their perceptions and satisfaction that will give the best-indicated system to understand consumer stability. For the accomplishment of this research, the survey was distributed to the public via online. The development of instruments based on the guideline of System Usability Scale (SUS), the reliable tools for measuring and evaluate a wide variety of products and services. Some modification in basic instruments was done to meet the requirement study. A full-fledged questionnaire was distributed among the 150 to 200 respondents to know their feedback on the food service delivery system in Malaysia. After the process of data cleaning, only 153 respondents included and considered for discussion and debate in this paper. The behaviour and user satisfaction level by using the online food services system will discuss further and some comparisons will be the main output of this research. Overall, most of the respondents satisfied with the service provided by Food Panda Service and Grab Food Service because the system easy to use and delivery time is equitable